Psychological aspects of students’ perception of control in foreign language learning - T. S. Putilovskaya; I. G. Tuchkova; E. V. Zubareva (Вестник университета)
The article studies psychological aspects of the perception by the State University of Management students of a complex control three-stage system, providing a full and comprehensive assessment of knowledge and skills acquired by students in foreign language learning. The authors briefly describe the control system itself, consider the principles of compiling an online survey and analyze the resulting students’ responses, revealing the peculiarities of their foreign language control activities perception. The conducted survey made it possible to identify the problems and difficulties faced by students during the exam session, analyze the factors affecting the psychological comfort state when doing assignments, and develop recommendations aimed at the control system further improvement. The purpose of the study is to maximize the control quality at all stages of foreign language learning. The student survey data show that the respondents objectively and positively perceive both the control format and its structural and content features. In addition, students adequately assess the tasks complexity level offered to them and the results of their own learning activities.